Enhancing Pedagogical Content Knowledge and Motivation in Pre-Service Music Teachers: Efficacy of the BMT-PCK Training Module - Jiang, Chuanxing; Ishak, Nor Asniza (Journal of Ecohumanism, 2025)
Pedagogical Content Knowledge is pivotal in music education, bridging content expertise and pedagogical skills to enhance teaching efficacy and student learning outcomes. This study combines basic music theory with PCK, and uses the ADDIE model to design a BMT-PCK training module for pre-service music teachers. This module is designed to improve pre-service music teachers' pedagogical knowledge, content knowledge, instructional strategies, and teaching motivation. The participants were 40 pre-service music teachers preparing for work in Hunan Province, China, assessing changes through pre- and post-intervention tests and surveys. The tests for assessing pedagogical knowledge and content knowledge gains. Surveys, based on validated scales, measure shifts in teaching motivation and effectiveness. Findings indicate significant improvements in participants' pedagogical understanding, content knowledge, and motivational levels. These results demonstrate the effectiveness of the BMT-PCK module in enhancing the competence of pre-service music teachers and provide a scalable model for future pre-service music teacher training programs.